Fear of cancer recurrence inventory (FCRI) in Spanish: validation in Mexican women with breast cancer - Juárez-García, Dehisy Marisol; Vázquez-Esseso, Mónica Beatriz; Gálvez-Hernández, Lizette; Bazan, Jorge; Simard, Sébastien (Anales de Psicología / Annals of Psychology, 2024)
Background/Objective. The Fear Cancer Recurrence Inventory (FCRI) evaluates fear cancer recurrence multidimensionally and proposes a clinical cutoff point. However, there has yet to be a translated Spanish version of the FCRI to date. This study aims to evaluate the psychometric properties of the Spanish version of the FRCI in women who completed primary treatment for breast cancer. Material and Methods. Recommendations of the International Test Commission were followed for cultural adaptation. Two hundred sixty-seven women who completed primary treatment for breast cancer participated in and responded to the Spanish version of the FCRI and the Supportive Care Needs Survey. Results. Two models are explored using AFC, the second order model χ2 (807, n = 265) = 1500.3, p < .001, χ2/gl = 1.85, CFI = .89, TLI = .89, RMSEA = .057 (90% confidence interval = .052–.061), and the seven related factors model χ2 (791, n = 265) = 1391.7, p < .001, χ2/gl = 1.75, CFI = .91, TLI = .90, RMSEA = .053 (90% confidence interval = .049–.058) obtained an optimal fit. Adequate-to-good Cronbach’s alpha values and the interclass correlation index were acceptable for five of the seven dimensions (.68 to .83). Conclusion. The Spanish version of the FCRI has psychometric properties suitable for clinical and research use in Mexican populations.